URBAN GREENING AS A COOLING TOOL TOWARDS THE HEAT ISLAND EFFECT - Bubik, Anja; Kolar, Lucija (Journal of Energy Technology, 2024)
Roofs, as the top layer of the urban environment, significantly contribute to overheating and creating a heat island, which is known as one of the most critical global warming effects. There are several ways to mitigate the effects of such heat islands, among which greening is the most natural, sustainable solution, and also economically acceptable and socially valued principle. Vegetation is known to significantly improve the urban microclimate and directly reduce the effect of the urban thermal core. At the Environmental Protection College in collaboration with the Institute Complementarium, both based in Slovenia, we conducted a pilot experiment to evaluate greening, in our case the principle of a flat green roof, as an effective and promising approach for reducing an urban heat island and its effects. Temperature measurements have shown that the green surface can lower both the surface temperature itself (e.g., the roof) and the air surrounding the green surface. We have presented an initial pilot case, which is planned to be upgraded in the future to confirm our current results and assumptions. In addition, we summarized data showing that Velenje is, in view of annual higher average temperatures, a highly suitable urban environment for the introduction of greening principles on the top urban layers.